2020
DOI: 10.1016/j.xkme.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Potassium Restrictions in CKD on Clinical Outcomes: Benefits of a Plant-Based Diet

Abstract: In patients with advanced-stage chronic kidney disease (CKD), progressive kidney function decline leads to increased risk for hyperkalemia (serum potassium > 5.0 or >5.5 mEq/L). Medications such as renin-angiotensin-aldosterone system inhibitors pose an additional hyperkalemia risk, especially in patients with CKD. When hyperkalemia develops, clinicians often recommend a diet that is lower in potassium content. This review discusses the barriers to adherence to a low-potassium diet and the impact of dietary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 94 publications
(162 reference statements)
0
28
1
4
Order By: Relevance
“…However, in certain circumstances, such as an excess consumption of diuretics or during high levels of diarrhea or vomiting, a person can have hypokalaemia that, if detected, can be easily solved by Mg and K supplementation and/or adequate diet [ 302 ]. Moreover, a decrease in potassium concentration in basic foods has been detected in some countries, such as the USA, South Korea, and Mexico, where people living in food-insecure households owing to low income and poor diets and low consumption of fruits and vegetables have health problems associated with potassium deficiency [ 303 , 304 , 305 , 306 ]. Adequate levels of K + intake in humans are associated with a decreased risk of several important pathologies, such as high blood pressure [ 307 , 308 ] and cardiovascular [ 307 , 308 ] and renal diseases [ 307 ].…”
Section: K and Food Security And Human Healthmentioning
confidence: 99%
“…However, in certain circumstances, such as an excess consumption of diuretics or during high levels of diarrhea or vomiting, a person can have hypokalaemia that, if detected, can be easily solved by Mg and K supplementation and/or adequate diet [ 302 ]. Moreover, a decrease in potassium concentration in basic foods has been detected in some countries, such as the USA, South Korea, and Mexico, where people living in food-insecure households owing to low income and poor diets and low consumption of fruits and vegetables have health problems associated with potassium deficiency [ 303 , 304 , 305 , 306 ]. Adequate levels of K + intake in humans are associated with a decreased risk of several important pathologies, such as high blood pressure [ 307 , 308 ] and cardiovascular [ 307 , 308 ] and renal diseases [ 307 ].…”
Section: K and Food Security And Human Healthmentioning
confidence: 99%
“…Studies have shown that the risk ratio for the progression of CKD was 1.59 in patients with a high-potassium diet compared to those with a low-potassium diet [19] . Excessive limitation of potassium intake may lead to hypokalemia [20] , malnutrition [21] , and increased risk of poor prognosis [22] . However, a study showed a controversial finding that dietary potassium was not associated with serum potassium levels [23] .…”
Section: The Impacts Of Diuretics Raas Indicators and Low Raaq Scorementioning
confidence: 99%
“…Studies have shown that the risk ratio for the progression of CKD was 1.59 in patients with a high-potassium diet compared to those with a low-potassium diet [19] . Excessive limitation of potassium intake may lead to hypokalemia [20] , malnutrition [21] , and increased risk of poor prognosis [22] . However, a study showed a controversial nding that dietary potassium was not associated with serum potassium levels [23] .…”
Section: The Impacts Of Diuretics Raas Indicators and Low Raaq Scorementioning
confidence: 99%